Effects of a 12-week training program in outdoor gym equipment in morphological and functional parameters, quality of life, and physical activity levels in older adults - Barbosa, Welmo A.; Machado, Alexandre F.; Bergamin, Marco; Gobbo, Stefano; Bullo, Valentina; Pontes Junior, Francisco Luciano; Evangelista, Alexandre L.; Scartoni, Fabiana R.; Rica, Roberta L.; Bocalini, Danilo S. (Frontiers in Sports and Active Living, 2024)
Introduction This study aimed to investigate the effectiveness of a supervised physical training program with controlled cadence on functional fitness parameters, quality of life perception, and physical activity level in older adults. Methods Sixty physically independent older adults were randomly divided into three groups: Supervised Training (ST, n = 20), Unsupervised Training (UT, n = 20), and a Control Group (C, n = 20). The ST and UT groups participated in a 12-week program, performing exercises three times a week for 30 min. The ST group had structured weekly sessions consisting of a 5-minute warm-up (walking at 60% of max heart rate), 20 sets of 30 s at a moderate pace controlled by a metronome with 30 s of passive recovery, and a 5-minute cool-down on non-consecutive days. The UT group trained spontaneously using senior gym equipment, including elliptical machines, rowing machines, air skiers, and leg press machines. The control group maintained their usual daily routines throughout the study. Parameters evaluated included body mass, body mass index (BMI), muscle thickness (biceps brachii, triceps brachii, and vastus lateralis), and functional capacity tests (walking 10 m [W10 m], rising from a sitting position [RSP], rising from the prone position [RVDP], sitting and rising from a chair and moving around the house [SRCW]). Quality of life was assessed across physical, psychological, environmental, and social domains, and physical activity levels were also measured. Results No significant changes (p > 0.05) in body mass, BMI, or muscle thickness were observed between groups before and after the intervention. However, significant time effects in functional fitness tests were found only in the ST group for W10 m (p = 0.0469), RVDP (p < 0.0004), RSP (p < 0.0001), and SRCW (p < 0.0001). Quality of life improved significantly over time in the ST and UT groups across all domains (p < 0.0001). Both ST and UT groups also showed significant increases in weekly physical activity time (p > 0.0001). Conclusion 12 weeks of training improved quality of life perception and physical activity levels in older adults.